2010
DOI: 10.1061/(asce)gt.1943-5606.0000285
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Analysis for Spatially Referenced Roller-Integrated Compaction Measurements

Abstract: An approach to quantify nonuniformity of compacted earth materials using spatially referenced rollerintegrated compaction measurements and geostatistical analysis is discussed. Measurements from two detailed case studies are presented in which univariate statistical parameters are discussed and compared to geostatistical semivariogram modeling parameters and analysis. The univariate and geostatistical parameter values calculated from the roller-integrated measurements are also compared to traditional spot test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…Numerous different indicators such as Compaction Meter Value (CMV), Resonance Meter Value, Continuous Compaction Value, Omega value, and machine drive power have been proposed to gauge the compaction state of the soil through the spectrum analysis of the vibration signal (White & Thompson, ; Xu & Chang, ). Meanwhile, research has been reported on the theory of the compaction process (Beainy, Commuri, & Zaman, ; Beainy, Commuri, Zaman, & Syed, ), the spatial distribution (Vennapusa, White, & Morris, ; Xu & Chang, ), the prediction model based on neural networks (Beainy, Commuri, & Zaman, ; Commuri, Mai, & Zaman, ), and the automatic control of compaction quality (Xu, Chang, & Gallivan, ). However, some researchers have questioned the accuracy of CCC‐ and IC‐measured indicators because the correlation coefficient between these indicators and compaction quality is not very high (Meehan, Cacciola, Tehrani, & Iii, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous different indicators such as Compaction Meter Value (CMV), Resonance Meter Value, Continuous Compaction Value, Omega value, and machine drive power have been proposed to gauge the compaction state of the soil through the spectrum analysis of the vibration signal (White & Thompson, ; Xu & Chang, ). Meanwhile, research has been reported on the theory of the compaction process (Beainy, Commuri, & Zaman, ; Beainy, Commuri, Zaman, & Syed, ), the spatial distribution (Vennapusa, White, & Morris, ; Xu & Chang, ), the prediction model based on neural networks (Beainy, Commuri, & Zaman, ; Commuri, Mai, & Zaman, ), and the automatic control of compaction quality (Xu, Chang, & Gallivan, ). However, some researchers have questioned the accuracy of CCC‐ and IC‐measured indicators because the correlation coefficient between these indicators and compaction quality is not very high (Meehan, Cacciola, Tehrani, & Iii, ).…”
Section: Introductionmentioning
confidence: 99%
“…A major advantage of the data that is recorded by CCC and IC systems is that measurements can be made much more continuously than with traditional spot-measurement tests such as the nuclear density gauge test or sand cone test. Consequently, CCC or IC measurements are sometimes considered to represent 100% coverage of the compacted area (e.g., Vennapusa et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A relationship documented by White et al (2007b) for a granular base material (classified as A-1-b) between CMV and Keros 200-mm plate diameter LWD device (E LWD-K2 ) is presented in the figure as a reference. The E LWD-K2 and E LWD-D2 measurements are strongly correlated and are close to R 2 = 1 line (see Vennapusa and White 2008b). Another regression line is plotted on Figure 5.9 for E LWD-Z2 based on a relationship documented by Vennapusa and White (2008b) between E LWD-K2 and E LWD-Z2 measurements (E LWD-K2 = 1.75 E LWD-Z2 ).…”
Section: Comparison Of Roller-integrated and In-situ Point Measurementsmentioning
confidence: 62%
“…The E LWD-K2 and E LWD-D2 measurements are strongly correlated and are close to R 2 = 1 line (see Vennapusa and White 2008b). Another regression line is plotted on Figure 5.9 for E LWD-Z2 based on a relationship documented by Vennapusa and White (2008b) between E LWD-K2 and E LWD-Z2 measurements (E LWD-K2 = 1.75 E LWD-Z2 ). Although there is scatter, the E LWD-D2 and E LWD-Z2 measurements matched the trend of existing relationships.…”
Section: Comparison Of Roller-integrated and In-situ Point Measurementsmentioning
confidence: 62%
See 1 more Smart Citation